The influence of aerobic training on body composition in premenopausal women undergoing endocrine therapy for breast cancer - Hojan, Katarzyna; Milecki, Piotr (Contemporary Oncology/Współczesna Onkologia, 2011)
Aim of the study : The objective of the study was to determine the body composition (BC) changes in women with breast cancer after endocrine therapy, and the influence of aerobic training on the parameters under discussion. Material and methods : 41 women aged 32-48 (mean ± SD 44.1 ±4.4) with breast cancer during endocrine therapy (ET). This was a nonrandomized, prospective trial. The following examinations were conducted in patients according to the schedule: I before the beginning of ET; II after 6 months of the ET; III after 12 months of ET and after 6-month aerobic training. Body composition was evaluated using dual X-ray absorptiometry (DEXA) with respect to free fatty mass, lean, fat and the percentage location of android and gynoid fat. The body build was evaluated with respect to body height, body weight and selected anthropometric parameters BMI and WHR. Results : During the first six months of ET without regular physical activity the following was reported: a significant increase of body weight, BMI, the amount of fatty tissue, including android fat distribution (p 0.05). At that time muscle (p 0.05) reductions were reported. After the six-month aerobic workout no significant body weight or BMI increase was observed. However, there was a significant reduction in WHR (p < 0.05), which correlated with the decrease of android fatty tissue (p < 0.05). The other elements evaluated in the DEXA underwent statistically insignificant changes. Conclusions : The outcome analysis allows us to conclude that during breast cancer ET the patients are reported to have negative changes in BC and physique. Therefore, this patient group is advised to receive regular rehabilitation with the aim of reducing the side effects of the treatment. However, aerobic training seems to be insufficient in order to fully reduce the side effects of this form of cancer therapy.